Transforming introductory psychology : expert advice on teacher training, course design, and student success - Gurung, Regan A. R.; Neufeld, Garth (American Psychological Association, 2022)
"Each year, well over a million undergraduate students take an introductory psychology course. This edited volume presents recommendations for designing and teaching this important course. The recommendations stem from an initiative of the American Psychological Association, which seeks to make introductory psychology a transformational experience for students. While some students taking the course will become psychology majors or even psychologists, most will pursue other careers. Thus, successful introductory psychology courses help students grow personally, academically, and professionally with skills that will be valuable for the rest of their lives, regardless of career. The book's recommendations cover four key areas: course design, defining and assessing student learning goals and outcomes, teacher training and development, and student learning and transformation. Chapters illustrate how to implement the recommendations in various institutions, including public and private colleges and universities, research universities, liberal arts colleges, comprehensive universities, two-year colleges, and high school. Given the diverse purposes served by the introductory psychology course, this work is a must-have for every psychology department and every person who teaches introductory psychology"--